Left ventricular hypertrabeculation in Ebstein anomaly – a clinically significant or irrelevant problem?. (14th October 2021) - Cieplucha, A; Trojnarska, O; Rajewska-Tabor, J; Katarzynska-Szymanska, A; Mitkowski, P; Pyda, M
Abstract: Background: Ebstein anomaly (EA) is characterized by anomalous tricuspid valve resulting in the whole right heart's distorted anatomy. Heart failure is the most frequent complication in adults with EA. Recently more attention is also paid to the left ventricle. Some limited echocardiographic data suggest a markedly increased occurrence of the left ventricular hypertrabeculation, by some authors called a non-compacted myocardium. Currently, cardiac magnetic resonance (CMR) is a gold standard in the evaluation of hypertrabeculation. However, different diagnostic criteria and discrepancies in the study outcomes make the clinical interpretation of this phenomenon questionable and challenging. Purpose: To determine the frequency of the left ventricular hypertrabeculation among adults with EA; to assess its association with the ventricular size and function and the markers of heart failure. Methods: Study group consisted of 35 unoperated adults (mean age 41.9±14.8 years) with Ebstein anomaly. The study protocol included: a) cardiac magnetic resonance (CMR) with the assessment of the left ventricle (LV) and functional right ventricle (fRV), including ejection fraction (EF), end-diastolic, end-systolic, and stroke volumes indexed by body surface area (respectively: EDVind, ESVind, SVind), and presence of hypertrabeculation defined according to Jacquier (1) as trabeculation mass >20% of the LV mass; b) cardiopulmonary tests with the assessment of peak oxygen consumption (peak VO2, % of predicted peak VO2), ventilation/carbon dioxide slope (VE/VCO2 slope) c) brain natriuretic peptide (BNP). Results: Left ventricular hypertrabeculation was present in 13 (37.1%) patients. We demonstrated no difference between patients with and without LV hypertrabeculation regarding: s the left ventricular size and function [LV EDV ind (ml/m 2 ): 65.9±11.2 vs. 67.8±16.6, p=0.737; LV SV ind (ml/m 2 ): 37.4±8.6 vs. 40.1±9.5, p=0.48; LV EF (%): 56.9±8.6 vs. 59.9±7.9, p=0.415]; the right ventricular size and function [fRV EDV ind (ml/m 2 ): 147.8±71.1 vs. 126.9±42.2, p=0.438; fRV SV ind (ml/m 2 ): 22.0±16.4 vs. 29.2±11.9, p=0.302; fRV EF (%): 38.0±12.0 vs. 46.0±10.4, p=0.184]; the heart failure markers, including cardiopulmonary parameters [peakVO2 (ml/kg/min): 25.0±5.8 vs. 25.4±5.1, p=0.855; % peak VO2: 69.4±15.5 vs. 78.9±23.1, p=0.284; VE/VCO2slope: 24.4±2.5 vs. 25.9±4.1, p=0.332] and BNP [52.1±40.3 vs. 59.3±41.8 (pg/ml), p=0.663]. Conclusions: Left ventricular hypertrabeculation demonstrated by cardiac magnetic resonance is a phenomenon frequently occurring among adults with Ebstein anomaly. However, its presence is not associated with both ventricles' worse function nor with reduced exercise capacity. Therefore, the clinical relevance of left ventricular hypertrabeculation in this population remains questionable and requires further prospective studies. Funding Acknowledgement: Type of funding sources: None.